A new functional classification of U.S. metropolitan and micropolitan areas - Robert W. Pendergrass (PLoS ONE, 2025)
This study develops a new functional classification of metropolitan and micropolitan areas in the United States. The methodology used was based on the widely used locational quotient and the Coefficient of Specialization (also known as the Index of Divergence). Determining a specialty or which industrial category may be dominant was set to be the outliers above the upper inner fence for each distribution. The units of analysis were all 927 United States metropolitan and micropolitan areas, excluding Puerto Rico. Readily available employment data from the American Community Survey for 2021 was used. Issues and problems with previous classification systems, such as the reliance on a small number of large cities, the inclusion of unpublished data, and subjectivity, were avoided. A relatively small number of urban areas were found to have multiple functional specializations: only forty-five (4.9% of all areas) had two or more functional specialties. Only five had three functional specialties (just over half a percent). Diversified Metro/Micro Areas, which had no industrial category that stood out as dominant, was the single largest class. The pattern of employment for metropolitan areas that specialized in the Productive Class diverged the most from the overall national pattern of metropolitan areas. Those areas in the Extractive Class followed with the second highest degree of divergence.